Structural plasticity and hippocampal function.[article]. - Leuner, Benedetta; Gould, Elizabeth
The hippocampus is a region of the mammalian brain that shows an impressive capacity for structural reorganization. Preexisting neural circuits undergo modifications in dendritic complexity and synapse number, and entirely novel neural connections are formed through the process of neurogenesis. These type of structural change were once thought to be restricted to development. However, it is now generally accepted that the hippocampus remains structurally plastic throughout life. This article reviews structural plasticity in the hippocampus over the life span, including how it is investigated experimentally. The modulation of the structural plasticity by various experientialfactors as well as the possible role it may have in hippcampal functions such as learning and memory, anxiety, and stress regulation are also considered. Although significant progress has been made in many of these areas, we highlight some of the outstanding issues that remain.
Keywords: Adult neurogenesis; Anxiety; Learning; Memory; Synapse